SYNTHESIS OF THE ADAPTIVE NEURONETWORK REGULATOR OF THE AVIATION GAS-TURBINE ENGINE - Єнчев, С.; Гашко, А. (Science-based technologies, 2012)
The analysis of methods construction multimode regulators is conducted for the aviation engine running, and also construction of their analogues on the basis of neurons networks. The task of synthesis of structure of neurons networks regulator of aviation turbo-engine decides.